ANALISIS PERILAKU BRANDSWITCHING PEMBELIAN NOTEBOOK DI KOTA SEMARANG - Koencoro, Bambang; Marlien, Marlien (Jurnal Ilmiah Telaah Manajemen, 2009)
An experienceof using a particular product lead to special attitutude against the pruduct. Whether he or she experience good or bad feeling about the product. It makes the customer to be always aware that a knowledge about the product is very critical to make a good decision. Otherwise, it is inevitablyto easIly switch the brand the purpose of the study is to investigate the role of the prior experience and the knowledge about the brand to the customers satisfaction. Further to explore the impact to brandswitching, data summitted from respondens who bought and owned particular brand of notebook. The result show that the customer satisfaction is greatly influnced by the prior experience and product knowledge. In addition, a number of broad and retail search give impact brand switchig.Keyword : Brandswitching, Prior experience, customer satisfaction